Atimicrobial activity of potato aspartic proteases (StAPs) involves membrane permeabillization - Mendieta, Julieta Renee (2006)
Solanum tuberosum aspartic proteases (StAPs) with antimicrobial activity are induced after abiotic and biotic stress. In this study the ability of StAPs to produce a direct antimicrobial effect was investigated. Viability assays demonstrated that StAPs are able to kill spores of Fusarium solani and Phytophthora infestans in a dose-dependent manner. Localization experiments with FITC-labelled StAPs proved that the proteins interact directly with the surface of spores and hyphae of F. solani and P. infestans. Moreover, incubation of spores and hyphae with StAPs resulted in membrane permeabilization, as shown by the uptake of the fluorescent dye SYTOX Green. It is concluded that the antimicrobial effect of StAPs against F. solani and P. infestans is caused by a direct interaction with the microbial surfaces followed by membrane permeabilization.